2011
DOI: 10.1007/s12223-011-0009-1
|View full text |Cite
|
Sign up to set email alerts
|

Trk2 transporter is a relevant player in K+ supply and plasma-membrane potential control in Saccharomyces cerevisiae

Abstract: In Saccharomyces cerevisiae, TRK1 and TRK2 genes encode partially redundant K(+) transporters. Direct involvement in K(+) uptake has been shown for Trk1p since cells growing under limiting environmental K(+) concentrations demand its presence. The biological role of Trk2p is less understood. In our experiments, TRK2 overexpression improved the ability of trk1 cells to grow in low K(+) and led to a higher accumulation of K(+). Using diS-C(3)(3) as a potentiometric probe, we revealed a higher hyperpolarization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…This difference may result from the re‐uptake of lost K + by the wild‐type cells. Detailed analysis revealed that deletion of both TRK1 and TRK2 contributed to the hyperpolarization (both single mutants being more hyperpolarized than BY4741 but less hyperpolarized than the double mutant; Petrezselyova et al ., 2010a), suggesting that both systems are active and contribute to re‐uptake of lost potassium during starvation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference may result from the re‐uptake of lost K + by the wild‐type cells. Detailed analysis revealed that deletion of both TRK1 and TRK2 contributed to the hyperpolarization (both single mutants being more hyperpolarized than BY4741 but less hyperpolarized than the double mutant; Petrezselyova et al ., 2010a), suggesting that both systems are active and contribute to re‐uptake of lost potassium during starvation.…”
Section: Resultsmentioning
confidence: 99%
“…Deletion of TRK1 and TRK2 genes in strains with different genetic backgrounds and under various experimental conditions (Ko et al ., 1990; Ramos et al ., 1994; Madrid et al ., 1998; Bertl et al ., 2003) always results in inhibited growth at low K + concentrations, certain hyperpolarization of the plasma membrane and the observation of residual ectopic potassium transport. Whereas the phenotypes listed above are mainly connected to the deletion of TRK1 , the effect of TRK2 absence is much smaller, being almost negligible in some experimental conditions (Madrid et al ., 1998), or observable only in specific mutants (Michel et al ., 2006) and in certain reference strains (Bertl et al ., 2003; Petrezselyova et al ., 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…The activity of Trk1 has been described to be important for K + and pH homeostasis (Madrid et al, 1998;Yenush et al, 2002), turgor (Merchan et al, 2004) and plasma membrane potential (Δw) (Madrid et al, 1998;Mulet et al, 1999). Although the potassium uptake via Trk2 is much lower than via Trk1 in exponentially growing cells (Ramos et al, 1994), a recent study showed that Trk2 activity contributes significantly to the maintenance of membrane potential in growing cells (Petrezselyova et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The CBS573 (ATCC6258) C. krusei strain was used to amplify fragments of genomic DNA. A derivative of the S. cerevisiae BY4741 strain (MATa his3Δ1 leu2Δ0 met15Δ0 ura3Δ0 EUROSCARF), the BYT12 strain lacking its own potassium uptake systems (trk1Δ trk2Δ; Navarrete et al, 2010;Petrezselyova, Ramos, & Sychrova, 2011), was used to express cloned C. krusei DNA fragments.…”
Section: Strains Media and Growth Conditionsmentioning
confidence: 99%